Mid-IR standoff measurement of ageing-related spectroscopic changes in bitumen in the 6 µm (1700 cm−1) region. Part 1: measurement strategy and instrument design principles - Hodgkinson, Jane; Davis, Nicholas M.; Browne, Cormac; Nesnas, Kamal; McRobbie, Stuart; Wright, Alex; Tatam, Ralph P. (Springer, 2025)
A strategy is described to make in-situ measurements of a spectroscopic marker of ageing in bitumen binders used on asphalt-paved roads. Oxidation of bitumen at the surface increases the number of carbonyl (C=O) bonds, and this can be measured in the 6 μm region (1700 cm−1) of the mid-infrared. A measurement strategy is proposed to make standoff measurements of surface reflectivity in this region, despite the challenge presented by numerous strong absorption lines from atmospheric water vapour within the optical path. An instrument design is described to make measurements at 4 discrete laser wavelengths, namely 1593.0, 1641.4 and 1731.3 cm−1 (around 6 µm) and at 2633.6 cm−1 (3.8 µm), the first 3 responding to carbonyl absorption and the fourth acting as a spectral reference that is substantially unaffected by ageing. Part 2 of this paper describes the implementation of such an instrument and its experimental performance.
Keywords: 37 Earth Sciences; 3701 Atmospheric Sciences; 34 Chemical Sciences; Civil engineering; Infrared spectroscopy; Optical sensors